A Comprehensive Survey of the Harmony Search Algorithm in Clustering Applications - Abualigah, Laith; Diabat, Ali; Geem, Zong Woo (Applied sciences, 2020)
The Harmony Search Algorithm (HSA) is a swarm intelligence optimization algorithm which has been successfully applied to a broad range of clustering applications, including data clustering, text clustering, fuzzy clustering, image processing, and wireless sensor networks. We provide a comprehensive survey of the literature on HSA and its variants, analyze its strengths and weaknesses, and suggest future research directions.